Special Issue “Orthopaedic and Rehabilitation Engineering” - Joseph Mizrahi; Oron Levin (Applied Sciences, 2020)
This paper serves as an editorial preface to a Special Issue on Orthopaedic and Rehabilitation Engineering. The fields of Orthopaedic and Rehabilitation Engineering encompass a variety of topics. Perspectives on a variety of topics in these fields are presented, followed by a brief description of the contributions comprised in this Special Issue.